2006
DOI: 10.1074/jbc.m605707200
|View full text |Cite
|
Sign up to set email alerts
|

p53 Suppresses the Nrf2-dependent Transcription of Antioxidant Response Genes

Abstract: Cells respond to the shift of intracellular environment toward pro-oxidant conditions by activating the transcription of numerous "antioxidant" genes. This response is based on the activation of the Nrf2 transcription factor, which transactivates the genes containing in their promoters the antioxidant response cis-elements (AREs). If the oxidative stress provokes DNA damage, a second response of the cell takes place, based on the activation of p53, which induces cell cycle arrest and/or apoptosis. Here we have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
225
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(236 citation statements)
references
References 34 publications
8
225
2
1
Order By: Relevance
“…As mentioned before, under oxidative stress, p62 dissociates Nrf2 from Keap1 by direct competition, which subsequently activates Nrf2 and mediates the autophagic degradation of Keap1 (Faraonio et al 2006). The cross-talk between p62 and the Keap1-Nrf2 pathway in the regulation of autophagy may play an important role in the removal of ROS, prevention of oxidative damage and alleviation of ER stress during cerebral IR injury .…”
Section: Ischaemia and Strokementioning
confidence: 78%
See 1 more Smart Citation
“…As mentioned before, under oxidative stress, p62 dissociates Nrf2 from Keap1 by direct competition, which subsequently activates Nrf2 and mediates the autophagic degradation of Keap1 (Faraonio et al 2006). The cross-talk between p62 and the Keap1-Nrf2 pathway in the regulation of autophagy may play an important role in the removal of ROS, prevention of oxidative damage and alleviation of ER stress during cerebral IR injury .…”
Section: Ischaemia and Strokementioning
confidence: 78%
“…Conversely, DNA methylation by DNA methyltransferases (DNMTs) appears to downregulate the Nrf2 expression indirectly (Khor et al 2014;Yu et al 2010;Rajabi et al 2016;Tagde et al 2016b). (c) Accumulation of p21 and p62 disrupts the Nrf2-Keap1 complex: it has been demonstrated that p53 negatively regulates Nrf2 and specifically suppresses the transcription of target genes of Nrf2 (Faraonio et al 2006). p21 (a direct downstream target of p53) associates with the DLG motif of Nrf2, which leads to the disruption of Keap1 binding with Nrf2.…”
Section: Role Of the Nrf2-keap1 Pathway In Cancermentioning
confidence: 99%
“…In fact, our CKD animals treated with high dose of dh404 exhibited increased phosphorylated IKB and activation of NF k B pathway. Activation of NF k B, in turn, suppresses Nrf2 activity by preventing dissociation of Nrf2 from keap1 in the cytoplasm and by blocking Nrf2 binding to the antioxidant response elements of its target genes in the nucleus [56,57]. Thus excessive oxidative or covalent modification of keap1 leads to activation of inflammatory system and paradoxical inhibition of Nrf2, a scenario which is consistent with the divergent dose response to BARD analogs observed in CKD rats employed in the present study and in ApoE deficient mice with streptozotocin-induced diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…regulation of Nrf2 mediated by Kelch-like ECH-Associated Protein 1 (Keap1), recent pieces of evidence indicate that Nrf2 and p53 are functional competitors for the same DNA promoter regions [15], thereby identifying a new sophisticated level of control of Nrf2 trans-activation. In particular, it has been indicated that p53 binds to the antioxidant response elements (ARE), inhibiting, in such a way, Nrf2 transcriptional activity of the battery of genes involved in the antioxidant defense.…”
Section: Introductionmentioning
confidence: 99%